Small states: problems and opportunities in a world of rapid change - Kiribati - Baaro, B. (Ministry of Finance BairikiKI, 1991)
Looks briefly at the concept of smallness. Examines the problems of Kiribati such as geographical problems, distance from the markets, infertility of the soil, scarcity of resources, economic problems, and the environment. Also reviews the opportunities available.